2015
DOI: 10.1182/blood-2015-06-654780
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood T cells mediate enhanced antitumor effects compared with adult peripheral blood T cells

Abstract: Key Points• CB T cells mediate enhanced antitumor responses compared with PB T cells in a murine model of B-cell lymphoma.• The antitumor activity correlates with increased tumor-homing of CCR7 high CB CD8 1 T cells and rapid gain of cytotoxic and Th1 function. CD81 T cells and prompt induction of cytotoxic CD8 1 and CD4 1 T-helper (Th1) T cells in the tumor microenvironment. In contrast, in the PB group, this antilymphoma effect is impaired because of delayed tumoral infiltration of PB T cells and a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 56 publications
1
87
0
6
Order By: Relevance
“…These findings supported the hypothesis that a more potent GvL effect may be achieved after CBT. Hiwarkar et al 23 recently demonstrated that HLA-mismatch CB T cells mediated superior antitumor responses compared with T cells from donor PB using an experimental model, and this provocative study indicated that CB T cells were intrinsically more effective at GvL. In the present study, more recipients with HLA disparity (85% with 1-or 2-antigen mismatch) and the omission of ATG from the conditioning regimen (T cell replete) could both contribute to the robust GvL effect after CBT.…”
Section: Discussionmentioning
confidence: 99%
“…These findings supported the hypothesis that a more potent GvL effect may be achieved after CBT. Hiwarkar et al 23 recently demonstrated that HLA-mismatch CB T cells mediated superior antitumor responses compared with T cells from donor PB using an experimental model, and this provocative study indicated that CB T cells were intrinsically more effective at GvL. In the present study, more recipients with HLA disparity (85% with 1-or 2-antigen mismatch) and the omission of ATG from the conditioning regimen (T cell replete) could both contribute to the robust GvL effect after CBT.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 As timely IR seems essential in preventing RRM and NRM, strategies to improve IR to increase protection against viral disease and relapse of malignancy are warrented. 7,15,27,30 T-cell IR has been associated with the use, dose, and timing of serotherapy, indicating that a higher dose of serotherapy shortly before infusion of the graft is detrimental for timely and robust IR. 6,14,27,31,32 Thus, in vivo exposure of graft-infused T cells to serotherapy results in significant depletion of T cells and limits the exceptional proliferative capacity of cord blood T cells, as recently shown.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, the broader T-cell repertoire of reconstituting naive CD4 1 cells after CBT may have an additional advantage over BM and PBSCs, 39 as cord blood cells have an exceptional learning capacity despite their naivety and show a lower incidence of viral reactivation 30 and stronger antileukemic activity. 4,5,7 The high number of naive cells makes CBT a powerful platform for adjuvant cellular therapies (eg, cell vaccinations), 40,41 as the above-mentioned associations suggest that efficient priming of these cells may enhance antileukemic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 That cord blood T cells mediate enhanced antitumor effects, compared with adult peripheral blood T cells, was also recently shown in a xenograft Epstein-Barr virus lymphoma model. 6 For the optimal effect, prompt immune reconstitution is essential. The use of ATG in the conditioning is considered to be the major limitation for prompt immune reconstitution after UCBT.…”
Section: The Power Of Cord Blood Cells ------------------------------mentioning
confidence: 99%